How arsenic makes amorphous GeSe a robust chalcogenide glass for advanced memory integration. (September 2022) - Gu, Rongchuan; Xu, Meng; Qiao, Chong; Wang, Cai-Zhuang; Ho, Kai-Ming; Wang, Songyou; Xu, Ming; Miao, Xiangshui
Abstract: The 3D integration technology in semiconductor fabrication requires a key component, the ovonic threshold switching (OTS) selector, to suppress the current leakage. The As doped amorphous (a-) GeSe glass is a commercialized OTS material in 3D phase-change memory, but the understanding of such a doping mechanism is still inadequate. Here we systematically explore the effect of As doping on the structural, bonding, and dynamics properties of a-GeAsSe using ab initio molecular dynamics simulations. The results reveal that As atoms form strong bonds with both Ge and Se atoms. The distorted octahedral structures and the 5-fold rings linked by atoms are increased. All of these structural features lead to a more disordered configuration. Moreover, As atoms have notably slowed down the atomic mobility, rendering a-GeAsSe a high stability. Our studies offer insightful understanding of As-doping in OTS materials, paving the way for the design and application of advanced selector devices. Graphical abstract: The As doping leads amorphous GeAsSe to be a more disordered configuration, thus enhancing the stability of amorphous state Image, graphical abstract .